The Effect of Capital Structure, Profitability and Liquidity on the Company's Value in the Automotive Sub-Sector and Components for the Period 2017-2021 - Hasanudin Hasanudin (Enrichment : Journal of Management, 2022)
This research was conducted to determine the influence of Capital Structure, Profitability and Liquidity on Company Value using company time series panel data with a research period of 2017-2021. Using the panel data linear regression analysis method, with a sample of 9 companies from 13 automotive and component sub-sector companies in Indonesia. This research was analyzed using E views version 9 software with the results of the study, namely the capital structure proxiated by Debt Equity Ratio (DER) has a positive and significant effect on the Company's Value which is proxikan with Price to Book Value (PBV), Profitability produced by Return On Asset (ROA) has a negative and significant effect on the value of the Company proxikan with Price to Book Value (PBV) and Liquidity proxikan with Current Ratio (CR) have a positive and insignificant effect on the value of companies proxistivated with Price to Book Value (PBV).